1994
DOI: 10.1108/02686909410067570
|View full text |Cite
|
Sign up to set email alerts
|

The External Auditor′s Consideration of the Internal Audit Function

Abstract: Statement on Auditing Standards (SAS) 65 was issued in April 1991 to clarify various aspects of the working relationship that should exist between external and internal auditors. Describes the historical development of this relationship as viewed through the promulgation of authoritative literature, reports of official committees and commissions, and prior research. Presents a survey which describes various aspects and characteristics of this relationship in the light of the provisions of SAS 65.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Previous research on auditors' assessment of the criteria of IA competence includes: IA training programs, with an emphasis on professional certifications (Brown, 1983), and IA experience (Messier & Schneider, 1988). Other research has surveyed the IA, external auditor, CFO and audit committee, and found the Certified Internal Auditor designation (Myers & Gramling, 1997) or educational background of the IA (Reinstein, Lander, & Gavin, 1994) as the most important criterion of competence. The results of prior research suggest that the external auditor places greater reliance on IA with accounting/auditing qualifications and also finds that firms with IA are more likely to detect or deter financial statement fraud (e.g.…”
Section: Internal Audit Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research on auditors' assessment of the criteria of IA competence includes: IA training programs, with an emphasis on professional certifications (Brown, 1983), and IA experience (Messier & Schneider, 1988). Other research has surveyed the IA, external auditor, CFO and audit committee, and found the Certified Internal Auditor designation (Myers & Gramling, 1997) or educational background of the IA (Reinstein, Lander, & Gavin, 1994) as the most important criterion of competence. The results of prior research suggest that the external auditor places greater reliance on IA with accounting/auditing qualifications and also finds that firms with IA are more likely to detect or deter financial statement fraud (e.g.…”
Section: Internal Audit Characteristicsmentioning
confidence: 98%
“…Having unlimited access to IA's working papers facilitates external auditors' assessment of whether IA work is performed by competent persons. Reinstein et al (1994) find that external auditors access working papers to evaluate IA suggestions. Further, Felix et al (2001) find the availability and cooperation of the IA with the external auditor is associated with IA contribution to the financial statement audit.…”
Section: Internal Audit Activitiesmentioning
confidence: 99%
“…However, SAS 9 was criticized on the ground that it did not provide specific guidance for the accomplishment of this evaluation, leaving the degree of reliance up to the judgment of the individual auditors (Reckers and Lee, 1997). Thus, SAS 65 was issued in 1991 to clarify the working relationship that must exist between the external and internal auditors, and to provide increased guidance for external auditors on how to evaluate and test the internal auditor's objectivity, competence and work performance (Reinstein et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Zaman and Sarens (2013) found that even informal interactions between IAs and the AC enhance good corporate governance, and they (the authors) call for more research related to interactions amongst corporate governance partners. Reinstein et al (1994) pointed out that frequent meetings with IAs will alert the EAs to any operational and financial changes, as well as emerging issues pertaining to the clients, and at the same time, allow both sides an insight into the other's auditing techniques.…”
Section: Background and Motivationmentioning
confidence: 99%